ANALISIS VARIASI BAHASA PEREMPUAN PADA TOKOH LAKI-LAKI DAN PEREMPUAN DALAM FILM "JOSÉPHINE" - Putri Fajar Adinda, - (2019)
Tujuan dari penelitian ini adalah untuk mendeskripsikan secara empiris variasi bahasa perempuan yang direpresentasikan tokoh laki-laki dan perempuan, serta bagaimana penggunaan bahasa perempuan yang direpresentasikan oleh tokoh laki-laki dan perempuan dalam film "Joséphine". Penelitian ini menuggunakan metode pendekatan kualitatif dengan desain penelitian deskriptif karena data berupa kata dan kalimat. Berdasarkan hasil analisis, pada tokoh perempuan dalam film "Joséphine" ditemukan 9 dari 12 variasi bahasa perempuan, diantaranya lexical hedges or filler, tag question, rising intonation on declarative, 'empty' adjectives, intensifiers, hypercorrect grammar, emphatic stress, feedback and interruption dan gossip. Pada tokoh laki-laki ditemukan 8 dari 12 variasi bahasa perempuan, diantaranya lexical hedges or fillers,taq question, rising intonation on declarative, 'empty' adjectives, intensifiers, hypercorrect grammar, super-polite formsemphatic stress. Selain itu terdapat ketidaksesuaian penggunaan variasi bahasa perempuan yang direpresentasikan oleh tokoh laki-laki dan perempuan dalam film "Joséphine", seperti penggunaan tag question, 'empty' adjective, intensifiers, super-polite forms, avoidance of strong swear words dan intrruption. Ketidaksesuaian disebabkan oleh beberapa hal, diantaranya faktor sosial, adanya bahasa powerless atau powerful, serta situasi yang dihadapi oleh tokoh dalam film "Joséphine". Hasil penelitian ini dapat berkontribusi dalam memberikan informasi yang komperhensif mengenai fenomena variasi bahasa perempuan dalam sebuah film. Selain itu, diharapkan pula dapat memberikan sumbangsih dalam perkembangan khasanah keilmuan sosiolinguistik terutama kajian mengenai bahasa dan gender, dalam hal ini mengenai penggunaan variasi bahasa perempuan ----- The purpose of this study is to describe variations in women's language and how those variations were represented by male and female characters in film scripts presented by male and female characters in "Joséphine". This study used a descriptive qualitative research design. The data is collected by observation and note-taking technic. The findings of this study showed that there are 9 variations (of 12 of women's language of variations) on female characters, including lexical hedges or filler, tag question, rising intonation on declarative, 'empty' adjectives, intensifiers, hypper-correct grammar, emphatic stress, feedback and interruption and gossip. On the other hand, there are 8 variations (of 12 of women's language of variations) on male characters, including lexical hedges or fillers, taq question, rising intonation on declarative, 'empty' adjectives, intensifiers, hyppercorrect grammar, super-polite forms,emphatic stress and intrruption. However, this study found 6 mismatches in the use of several women's language variations represented by male and female characters, including; the use of tag question, 'empty' adjective, intensifiers, super-polite forms, avoidance of strong swear words and intrruption. The discrepancy is caused by several things, including the form of powerless and powerful language and social factors and the situation faced by the characters in Josephine's film. This study is expected to providing comprehensive information about the phenomenon of women's language variation in a film. In addition, it is also expected to be able to contribute in the development of sociolinguistic scientific, especially the study of language and gender, in this case concerning the usage of women's language variations